Hungarian Monitoring, 24 May 1989 . [Magyar rádiófigyelő], 1989. május 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports concerning events in China - New twists in Gldyan-Ivanov case in USSR - Weizsäcker's speech on anniversary of declaration of FRG constitution - Baltic republics' demands Domestic Affairs: - Miklós Németh's one-day work visit to Czechoslovakia - Agreed during Gyula Horn's Belgrade talks that Yugoslavia will hand over to Hungary archival documents pertaining to events of 1956 - State prosecutor Schmidt's opinion that bringing elections forward will do no good, recommends mixed electoral system of individual voting districts and party lists - Deputy president of Academy of Sciences: Ófalu not suitable for isotope storage - 12 GDR citizens allegedly demand resettlement in West Germany at FRG embassy in Budapest Economy: - Budget deficit will be three times larger than planned - Ferenc Vissi, vice-president of Pricing Office, on unsuccessful anti-inflation policy - Talks with IMF who suspended promised partial loan payment in mid-May Külpolitika: - A kínai eseményekkel kapcsolatos tudósítások - Tovább gyűrűzik a SZU-ban a Gldjan-Ivanov-ügy - Weizsäcker beszéde az NSZK-alkotmány kihirdetésének évfordulóján - A baltikumi köztársaságok követelései Belpolitika: - Németh Miklós egynapos csehszlovákiai munkalátogatása - Horn Gyula belgrádi tárgyalásain megállapodtak, hogy Jugoszlávia átadja Magyarországnak az 1956-os eseményekkel kapcsolatos levéltári dokumentumokat - Schmidt államjogász véleménye szerint a választások előrehozása semmi jót nem hozna. Kombinált választási rendszert javasol, egyéni választókerülettel és a pártok listáival - Ófalu térsége nem alkalmas izotópok tárolására, mondja az Akadémia alelnöke - Állítólag 12 NDK-állampolgár a NSZK budapesti nagykövetségén Nyugat-Németországba való áttelepülését követeli Gazdaság: - A költségvetés hiánya a tervezettnek háromszorosa lesz - Vissi Ferenc az Árhivatal elnöke az antiinflációs politika sikertelenségéről - Egyeztető tárgyalások a Nemzetközi Valutalappal, amely május közepén felfüggesztette a megígért hitel részlet kifizetését